Modified zinc negative electrode material for aqueous zinc ion battery as well as preparation method and application of modified zinc negative electrode material
The preparation of zinc metal foil with twin surface defects through mechanical pressurization process solves the problem of poor circulation stability of zinc foil negative electrode material, achieves the improvement of orderly zinc deposition and carrier transport, and significantly improves the electrochemical performance of the battery.
Patent Information
- Application Number
- CN202510074040.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-22
AI Technical Summary
The existing zinc foil negative electrode materials are uncontrollable during charging and discharging, resulting in poor cycling stability of the battery.
Zinc metal foil with twin surface defects is prepared by mechanical pressurization process, and the orderly deposition of zinc during charging and discharge is regulated, and carrier transport is enhanced.
The cyclic stability and electrochemical performance of zinc negative electrode materials have been significantly improved, with 58 times and 20.4 times of commercial zinc foils, and the corrosion resistance and rate performance have also been greatly improved.
Smart Images

Figure CN119864409A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a zinc negative electrode material for an aqueous zinc ion battery and a preparation method thereof, and belongs to the technical field of electrode material modification. Background Art
[0002] Energy demand is growing, and clean energy technology is developing. Compared with traditional lead-acid batteries and nickel-metal hydride batteries, aqueous zinc-ion batteries have higher energy density, are safer and more environmentally friendly, and have lower costs. They are a new energy storage technology that has attracted much attention in recent years. The negative electrode material of aqueous zinc-ion batteries usually uses zinc foil, and its theoretical specific capacity is 820mAh g -1 , the redox potential is -0.76V (vs SHE), and the application potential is huge. However, the growth of zinc dendrites in commercial zinc foil is uncontrollable during the charge and discharge process, resulting in poor cycle stability of the battery. Summary of the invention
[0003] The present invention aims to solve the technical problem of poor cycle stability of existing zinc foil negative electrode materials, and provides a modified zinc negative electrode material for aqueous zinc ion batteries and a preparation method thereof. The zinc negative electrode material of the present invention deposits zinc in an orderly manner during the charge and discharge process, thereby improving the cycle stability of the material.
[0004] The modified zinc negative electrode material for aqueous zinc ion batteries of the present invention is a zinc foil having a twin plane defect structure on the surface;
[0005] Furthermore, the surface roughness of the zinc foil is 10 to 50 nanometers;
[0006] Furthermore, the thickness of the zinc foil is 50 to 200 microns;
[0007] Furthermore, the purity of the zinc foil is 99.99% to 100%.
[0008] The preparation method of the modified zinc negative electrode material for the aqueous zinc ion battery is carried out according to the following steps:
[0009] The zinc metal is placed in a mechanical press, and is pressed vertically downward for 1 to 5 minutes under a pressure of 12 to 18 MPa to obtain a modified zinc negative electrode material for an aqueous zinc ion battery.
[0010] The application of the modified zinc negative electrode material for aqueous zinc ion batteries is to use it in aqueous zinc ion batteries.
[0011] The invention adopts a mechanical pressing process to prepare a zinc metal foil with twin surface defects, which is used in an aqueous zinc ion battery. During charging and discharging, the orderly deposition of zinc can be regulated, the carrier transport can be enhanced, the cycle stability of the material can be improved, and the electrochemical performance of the material can be greatly improved. The modified zinc negative electrode for an aqueous zinc ion battery of the invention has a current density of 5 mA cm-2 , surface capacity is 1 mAh cm -2 The charge-discharge cycle can be stably maintained for 3190 hours under the condition of 50 mA cm-2, which is 58 times that of the commercial zinc foil negative electrode. -2 , surface capacity is 1 mAh cm -2 Under the same conditions, the battery can be stably charged and discharged for 24,450 times, which is 20.4 times that of the commercial zinc foil negative electrode. The button-type aqueous zinc ion full battery assembled with the modified zinc negative electrode of the present invention and the layered manganese dioxide positive electrode material has a discharge capacity of 81 mAh g after 200 charge and discharge cycles at a 1C rate. -1 , which is 2.13 times that of commercial zinc foil anode.
[0012] The preparation method of the modified zinc negative electrode material provided by the present invention is green and pollution-free, low in cost, high in efficiency, and can realize large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is an X-ray diffraction spectrum of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1;
[0014] Figure 2 This is the X-ray diffraction spectrum of commercial zinc foil;
[0015] Figure 3 is a scanning electron microscope image of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1;
[0016] Figure 4 This is a SEM image of a commercial zinc foil;
[0017] Figure 5 is an electron backscattered diffraction pattern of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1;
[0018] Figure 6 is the electron backscatter diffraction pattern of commercial zinc foil;
[0019] Figure 7 is an atomic force microscope image of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1;
[0020] Figure 8 This is an atomic force microscope image of a commercial zinc foil;
[0021] Fig. 9 This is a corrosion resistance test diagram of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1;
[0022] Fig.10 This is a corrosion resistance test chart of commercial zinc foil;
[0023] Fig.11is an in-situ optical image of zinc deposition characteristics on the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1;
[0024] Fig.12 is an in situ optical image of the zinc deposition characteristics on commercial zinc foil;
[0025] Fig.13 is a three-dimensional image of zinc deposited on the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1;
[0026] Fig.14 is a three-dimensional image of zinc deposited on commercial zinc foil;
[0027] Fig.15 is a surface scanning electron microscope image of zinc deposited on the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1;
[0028] Fig.16 is a cross-sectional scanning electron microscope image of zinc deposited on the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1;
[0029] Fig.17 This is a surface SEM image of zinc deposited on a commercial zinc foil;
[0030] Fig.18 is a cross-sectional SEM image of zinc deposited on a commercial zinc foil;
[0031] Fig.19 This is an X-ray diffraction test analysis spectrum of the induction effect of twin plane defects on the crystal plane orientation of deposited zinc in the modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1;
[0032] Fig. 20 This is an X-ray diffraction test analysis spectrum of the induced effect of the deposited zinc crystal plane orientation of commercial zinc foil;
[0033] Fig.21 This is the rate performance of the modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1;
[0034] Fig. 22 It is the rate performance of commercial zinc foil;
[0035] Fig.23 The modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1 is 5 mA cm -2 Cycling performance under current density;
[0036] Fig.24 Commercial zinc foil at 5mAcm -2 Cycling performance under current density;
[0037] Fig.25 The modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1 is 50 mA cm-2 Cycling performance under current density;
[0038] Fig.26 Commercial zinc foil at 50mAcm -2 Cycling performance under current density;
[0039] Fig. 27 This is a scanning electron microscope image of the layered manganese dioxide positive electrode material;
[0040] Fig.28 It is the X-ray diffraction spectrum of layered manganese dioxide positive electrode material;
[0041] Fig.29 The cycle performance diagram of an aqueous zinc ion battery assembled with a modified zinc negative electrode material for an aqueous zinc ion battery prepared in Example 1 and a layered manganese dioxide positive electrode material at a 1C rate;
[0042] Fig.30 This is a cycling performance diagram of an aqueous zinc-ion battery assembled with commercial zinc foil and layered manganese dioxide positive electrode materials at a 1C rate. DETAILED DESCRIPTION
[0043] In order to more clearly illustrate the technical solution of the present invention, the present invention will be further described in detail in conjunction with the accompanying drawings.
[0044] Embodiment 1: The preparation method of the modified zinc negative electrode material for aqueous zinc ion battery of this embodiment is carried out according to the following steps:
[0045] Zinc metal with a purity of 99.99% is placed in a mechanical press, pressurized vertically downward, and pressed for 2 minutes at a pressure of 12 MPa to obtain a modified zinc negative electrode material for an aqueous zinc ion battery.
[0046] The modified zinc negative electrode material for the aqueous zinc ion battery prepared in this embodiment is zinc foil with a thickness of 200 microns.
[0047] Taking commercial zinc foil as a comparison, the commercial zinc foil is produced by Dongguan Kelude Company. The product name is zinc foil, the product purity is 99.99%, and the model specifications are 0.02 mm thickness, 100 mm width, and 1 meter length.
[0048] The X-ray diffraction spectrum of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1 is as follows: Figure 1 As shown, the X-ray diffraction spectrum of commercial zinc foil is as follows Figure 2 As shown, from Figure 1 and Figure 2 It can be seen that the modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1 and the commercial zinc foil are both polycrystalline structures. Compared with the commercial zinc foil, the crystal plane orientation of the modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1 does not change.
[0049] The scanning electron microscope image of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1 is as follows Figure 3 The SEM images of commercial zinc foil are shown in Figure 4 As shown, from Figure 3 and Figure 4 It can be seen that compared with the commercial zinc foil, the grain boundaries of the zinc crystals of the modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1 are clearer. Figure 4 It can also be seen that there are micro defects on the surface of commercial zinc foil.
[0050] The electron backscattered diffraction pattern of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1 is as follows: Figure 5 The electron backscatter diffraction pattern of commercial zinc foil is shown in Figure 6 As shown, from Figure 5 It can be seen that the surface of the modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1 has a twin plane defect structure. Figure 6 It can be seen that there is no twin structure on the surface of commercial zinc foil.
[0051] The atomic force microscope image of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1 is as follows Figure 7 As shown in the AFM image of commercial zinc foil Figure 8 As shown, from Figure 7 , 8 It can be seen that compared with commercial zinc foil, the modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1 has a lower surface roughness, and the height difference between its highest peak and lowest valley is 36.5 nanometers, while that of commercial zinc foil is 971 nanometers.
[0052] The modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1 and commercial zinc foil were simultaneously subjected to corrosion resistance test. The specific steps are: first, the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1 and commercial zinc foil were placed in a 1 mol L -1 The modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1 was immersed in a zinc sulfate electrolyte for 3 days, taken out, rinsed and dried at room temperature, and then its surface was characterized by scanning electron microscopy to observe surface changes. Fig. 9 As shown in the SEM photos of commercial zinc foil after corrosion resistance test Fig.10 As shown, from Fig. 9 It can be seen that there is no obvious corrosion product on the surface of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1. Fig.10 It can be seen that there are obvious corrosion products on the surface of commercial zinc foil, indicating that the corrosion resistance of commercial zinc foil in electrolyte is poor.
[0053] Optical cells were assembled using the modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1 and commercial zinc foil. The mold of the optical cell was produced by Beijing Zhongke Wanyuan Company. The product name is in-situ dendrite test cell. The assembly method of the optical cell is to cut the negative electrode material into two rectangular pole pieces with a length of 10 mm and a width of 6 mm, place them in the groove of the mold, with the cross section to be observed facing upward, and separate the two pole pieces with a baffle with a thickness of 1 mm. Then, a concentration of 1 mol L -1 The zinc sulfate electrolyte was used for real-time cross-sectional observation of the zinc deposition characteristics on the negative electrode using an optical microscope. The test parameters were a current density of 20 mA cm -2 The test photos of the modified zinc negative electrode for aqueous zinc ion battery prepared in Example 1 during the reaction process are as follows: Fig.11 As shown in the test photos of commercial zinc foil during the reaction process Fig.12 As shown. Fig.11 It can be seen that the deposition morphology is uniform and flat, with no dendrite growth and no bubbles generated. Fig.12 It can be seen that dendrite growth and bubble generation are obviously observed in the commercial zinc foil during the reaction process.
[0054] The deposited negative electrode was characterized in three dimensions using an optical microscope. The test image of the modified zinc negative electrode for aqueous zinc ion battery prepared in Example 1 is as follows: Fig.13 As shown, from Fig.13 It can be seen that the deposition morphology is relatively flat. The test picture of the commercial zinc foil negative electrode is as follows Fig.14 As shown, from Fig.14 It can be seen that the deposition morphology of the commercial zinc foil negative electrode is very uneven. The surface and cross-section of the zinc deposition characteristics of the modified zinc negative electrode for aqueous zinc ion battery in Example 1 were observed using a scanning electron microscope. The surface scanning electron microscope photos are shown in FIG. Fig.15 The scanning electron microscope photo of the cross section is shown in Fig.16 As shown, from Fig.15 The surface morphology shows that the deposited zinc grows along the (002) crystal plane. Fig.16 The cross section shows that the deposited morphology is relatively dense. The surface and cross section of the zinc deposition characteristics after commercial zinc foil negative electrode deposition were observed using a scanning electron microscope. The surface scanning electron microscope photos are shown in Figure 2. Fig.17 The scanning electron microscope photo of the cross section is shown in Fig.18 As shown, from Fig.17 and Fig.18 From the surface and cross-sectional morphology, it can be seen that the deposition morphology is very uneven and dendrites are formed.
[0055] The modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1 and commercial zinc foil were used for quasi-in-situ experiments. -2The current density was 1, 2, and 4 mAh cm -2 After the surface capacity of zinc, X-ray diffraction test was carried out, and the test data are as follows Fig.19 As shown, from Fig.19 It can be seen that the twin plane defect structure can induce the deposited zinc to grow mainly on the (002) crystal plane. -2 The current density was 4 mAh cm -2 After the surface capacity of zinc, X-ray diffraction test was carried out, and the test data are as follows Fig. 20 As shown, from Fig. 20 It can be seen that the (101) crystal plane in the deposited zinc occupies a higher proportion.
[0056] The modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1 and commercial zinc foil were used as working electrodes to assemble a 2032-type button-type symmetrical battery, which consisted of a negative electrode shell, a working electrode, a diaphragm, a counter electrode, a gasket, a washer, and a positive electrode shell. The electrolyte was 100 μL with a concentration of 1 mol L -1 The rate performance was tested using a Xinwei battery tester with current densities of 1 / 2 / 5 / 10 / 20 / 30 / 40 / 50 / 60 mA cm -2 The charging (or discharging) time is 12 minutes, and each current density test is 20 cycles of charging and discharging.
[0057] Fig.21 is the rate performance of the modified zinc negative electrode for aqueous zinc ion battery prepared in Example 1; Fig.21 It can be seen that the twin plane defect structure regulates the reaction kinetics of the modified zinc negative electrode, and the modified zinc negative electrode material has good rate performance. Fig. 22 The rate performance of commercial zinc foil; Fig. 22 It shows that commercial zinc foil negative electrode materials can be tested to 20mAcm -2 When the steps are completed, a short circuit occurs and the rate performance is poor.
[0058] Fig.23 The modified zinc negative electrode for aqueous zinc ion battery prepared in Example 1 was used at a current density of 5 mA cm -2 , surface capacity is 1 mAh cm -2 Cycle performance diagram under the conditions of Fig.23 It can be seen that the modified zinc negative electrode for aqueous zinc ion battery prepared in Example 1 has a current density of 5 mA cm -2 , surface capacity is 1 mAh cm -2 Under the conditions of stable charge and discharge cycle for 3190 hours. Fig.24 For commercial zinc foil anode at a current density of 5 mA cm -2 , surface capacity is 1 mAh cm -2Cycle performance diagram under the conditions of Fig.24 It can be seen that the commercial zinc foil negative electrode material has a current density of 5 mA cm -2 , with a surface capacity of 1 mAh cm -2 Under these conditions, the stable charge and discharge cycle is only 55 hours.
[0059] Fig.25 The modified zinc negative electrode for aqueous zinc ion battery prepared in Example 1 was used at a current density of 50 mA cm -2 , surface capacity is 1 mAh cm -2 Cycle performance diagram under the conditions of Fig.25 It can be seen that the modified zinc negative electrode for aqueous zinc ion battery prepared in Example 1 has a current density of 50 mA cm -2 , surface capacity is 1 mAh cm -2 Under the same conditions, it can stably charge and discharge for 24450 times. Fig.26 For commercial zinc foil anode at 50mAcm -2 Cyclic performance diagram under current density; from Fig.26 It can be seen that the commercial zinc sheet negative electrode material has a current density of 50 mA cm -2 , surface capacity is 1 mAh cm -2 Under the conditions of , the stable charge and discharge cycle is only 1200 times.
[0060] The modified zinc negative electrode material for aqueous zinc ion batteries prepared in Example 1 and the commercial zinc foil were used as negative electrodes, and button-type aqueous zinc ion full batteries were assembled with the layered manganese dioxide positive electrode material, wherein Fig. 27 This is a scanning electron microscope image of layered manganese dioxide positive electrode material. Fig.28 This is the X-ray diffraction spectrum of layered manganese dioxide positive electrode material. Fig. 27 and 28 It can be seen that manganese dioxide has a flower cluster morphology composed of nanosheets and a layered phase structure. The cycle stability of the button-type aqueous zinc ion full battery at 1C rate was tested using a Xinwei battery tester. The voltage window was 1-1.8V and the current density was 308mAg based on manganese dioxide. -1 The cycle stability curve of the modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 1 is as shown in FIG. Fig.29 As shown, from Fig.29 It can be seen that after 200 charge and discharge cycles, the discharge capacity is still 81 mAh g -1 The cycle stability curve of commercial zinc foil anode is shown in Fig.30 As shown, from Fig.30 It can be seen that the discharge capacity of the commercial zinc foil anode is only 38 mAh g after 200 charge and discharge cycles. -1 .
[0061] Embodiment 2: The preparation method of the modified zinc negative electrode material for aqueous zinc ion battery of this embodiment is carried out according to the following steps:
[0062] Zinc metal with a purity of 99.99% is placed in a mechanical press, pressurized vertically downward, and pressed for 5 minutes at a pressure of 18 MPa to obtain a modified zinc negative electrode material for an aqueous zinc ion battery.
[0063] The modified zinc negative electrode material for the aqueous zinc ion battery prepared in this embodiment is zinc foil with a thickness of 150 microns.
[0064] The modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 2 was used as the negative electrode, and a button-type aqueous zinc ion full battery was assembled with a layered manganese dioxide positive electrode material. The cycle stability of the button-type aqueous zinc ion full battery at a 1C rate was tested using a Xinwei battery tester. The voltage window was 1 to 1.8 V, and the current density was 308 mAg in terms of manganese dioxide. -1 The modified zinc negative electrode material for aqueous zinc ion battery prepared in Example 2 obtained by testing still has a discharge capacity of 68 mAh g after 200 charge and discharge cycles. -1 .
[0065] Comparative Example 1: The preparation method of the modified zinc negative electrode material for an aqueous zinc ion battery in this comparative example is carried out according to the following steps: zinc metal with a purity of 99.99% is placed in a mechanical press, pressurized vertically downward, and pressed for 7 minutes at a pressure of 25 MPa to obtain a modified zinc negative electrode material for an aqueous zinc ion battery.
[0066] Comparative Example 2: The preparation method of the modified zinc negative electrode material for an aqueous zinc ion battery in this comparative example is carried out according to the following steps: zinc metal with a purity of 99.99% is placed in a mechanical press, pressurized vertically downward, and pressed for 0.5 minutes at a pressure of 10 MPa to obtain a modified zinc negative electrode material for an aqueous zinc ion battery.
[0067] The aqueous zinc ion battery prepared in Comparative Example 1 and Comparative Example 2 uses the modified zinc negative electrode material as the negative electrode, and assembles a button-type aqueous zinc ion full battery with the layered manganese dioxide positive electrode material. The cycle stability of the button-type aqueous zinc ion full battery at a 1C rate is tested using a Xinwei battery tester. The voltage window is 1-1.8V, and the current density is 308mAg in terms of manganese dioxide. -1 The modified zinc negative electrode material for aqueous zinc ion battery prepared in Comparative Example 1 obtained by testing has a discharge capacity of only 35 mAh g after 200 charge and discharge cycles. -1 The modified zinc negative electrode material for aqueous zinc ion battery prepared in Comparative Example 2 has a discharge capacity of only 40 mAh g after 200 charge and discharge cycles. -1The performance of Comparative Example 1 is worse than that of Examples 1 and 2 because the pressing pressure is too high and the pressing time is too long, which causes the material surface to melt and deform, resulting in a decrease in battery performance; while Comparative Example 2 has a twin structure that is not formed due to the pressing pressure being too low and the pressing time being too short, which also causes a decrease in battery performance.
Claims
1. A modified zinc negative electrode material for an aqueous zinc ion battery, characterized in that: The modified zinc negative electrode material is a zinc foil with a twin plane defect structure on the surface.
2. A modified zinc negative electrode material for aqueous zinc ion batteries according to claim 1, characterized in that: The surface roughness of zinc foil is 10 to 50 nanometers.
3. A modified zinc negative electrode material for aqueous zinc ion batteries according to claim 1 or 2, characterized in that: The thickness of zinc foil is 50 microns to 200 microns.
4. A method for preparing a modified zinc negative electrode material for an aqueous zinc ion battery according to claim 1, characterized in that: The method proceeds as follows: The zinc metal is placed in a mechanical press, and is pressed vertically downward for 1 to 5 minutes under a pressure of 12 to 18 MPa to obtain a modified zinc negative electrode material for an aqueous zinc ion battery.
5. The use of a modified zinc negative electrode material for an aqueous zinc ion battery according to claim 1, characterized in that: The application is to use the modified zinc negative electrode material for aqueous zinc ion batteries in aqueous zinc ion batteries.